Isolation and Characterization of Bacteria Colonizing Acartia tonsa Copepod Eggs and Displaying Antagonist Effects against Vibrio anguillarum, Vibrio alginolyticus and Other Pathogenic Strains - Zidour, Mahammed; Chevalier, Mickaël; Belguesmia, Yanath; Cudennec, Benoit; Grard, Thierry; Drider, Djamel; Souissi, Sami; Flahaut, Christophe (Frontiers in Microbiology, 2017)
Copepods represent a major source of food for many aquatic species of commercial interest for aquaculture such as mysis shrimp and early stages of fishes. For the purpose of this study, the culturable mesophilic bacterial flora colonizing Acartia tonsa copepod eggs was isolated and identified. A total of 175 isolates were characterized based on their morphological and biochemical traits. The majority of these isolates (70%) were Gram-negative bacteria. Matrix-assisted laser desorption/ionisation-time of flight-mass spectrometry (MALDI-TOF-MS) was used for rapid identification of bacterial isolates. Here, 58% of isolates were successfully identified at the genus level and among them, 54% were identified at the species level. These isolates belong to 12 different genera and 29 species. Five strains, identified as Bacillus pumilus, named 18 COPS, 35A COPS, 35R COPS, 38 COPS and 40A COPS, showed strong antagonisms against several potential fish pathogens including Vibrio alginolyticus, Vibrio angularum, Listeria monocytogenes and Staphylococcus aureus. Furthermore, using a differential approach, we show that the antimicrobial activity of the 35R COPS strain is linked primarily to the production of antimicrobial compounds of the amicoumacin family, as demonstrated by the specific UV-absorbance and the MS/MS fragmentation patterns of these compounds.